2021
DOI: 10.2196/29397
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Booster Engagement Following a Web-Based Brief Intervention for Alcohol Misuse Among National Guard Members: Secondary Analysis of a Randomized Controlled Trial

Abstract: Background Alcohol misuse is a major health concern among military members. Reserve component members face unique barriers as they live off base with limited access to behavioral health services. Web and app-based brief interventions are a promising means to improve access to treatment for those who misuse alcohol, with the use of booster sessions to enhance effectiveness, solidify gains, and reinforce changes. However, little is known about who will engage in booster sessions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The peer‐based booster seemed to be more effective than the web‐based booster for a broader range of hazardous and harmful alcohol use measures, although the study was not designed to have sufficient power to allow direct comparisons between the two booster options. In a recently published comprehensive examination of the factors related to engagement in booster sessions, we demonstrated that the peer booster approach led to significantly greater engagement in booster sessions than the web booster format, controlling for multiple other factors that were also significantly related to engagement in boosters including educational level, rank and income [56]. These findings point to the benefit of social support, as well as the potentially greater personalization of booster content, given that the peers were former military service people.…”
Section: Discussionmentioning
confidence: 99%
“…The peer‐based booster seemed to be more effective than the web‐based booster for a broader range of hazardous and harmful alcohol use measures, although the study was not designed to have sufficient power to allow direct comparisons between the two booster options. In a recently published comprehensive examination of the factors related to engagement in booster sessions, we demonstrated that the peer booster approach led to significantly greater engagement in booster sessions than the web booster format, controlling for multiple other factors that were also significantly related to engagement in boosters including educational level, rank and income [56]. These findings point to the benefit of social support, as well as the potentially greater personalization of booster content, given that the peers were former military service people.…”
Section: Discussionmentioning
confidence: 99%
“…If the level of engagement corresponds to decreases in alcohol use or consequences, then interventions can be improved to enhance the likelihood of engagement following principles of implementation science (Bauer & Kirchner, 2020;Becker et al, 2022). Previous studies have found that increased engagement predicts positive health-related behavior changes, including reductions in drinking (Carrà et al, 2017;Paz Castro et al, 2017;Donkin et al, 2011;Linke et al, 2007;Norman et al, 2019) and higher likelihood of follow-up responses (Coughlin et al, 2021;Eysenbach, 2005). However, no work has examined the impact of engagement on outcomes of an intervention for college student alcohol use in a methodological and empirical way.…”
mentioning
confidence: 99%